(untitled) (Annals of Medical Research, 2021)
Transient myeloproliferative disease (TMD) is among the main hematologic problems seen in neonates with Down syndrome (DS). It is usually self-limiting and results in spontaneous remission within 3 to 6 months. Characteristic signs of TMD are leukocytosis, thrombocytopenia, anemia, hepatosplenomegaly, cutaneous nodules, and increased numbers of circulating blasts. In this article, we present a DS neonate without leukocytosis who was diagnosed as having TMD after a diffuse vesiculopapular eruption on the face, which is a different clinical presentation than other cases in the literature. Our aim is to emphasize the importance of early diagnosis and close multidisciplinary monitoring of these patients.